1999
DOI: 10.1126/science.285.5426.409
|View full text |Cite
|
Sign up to set email alerts
|

An Allele of COL9A2 Associated with Intervertebral Disc Disease

Abstract: Intervertebral disc disease is one of the most common musculoskeletal disorders. A number of environmental and anthropometric risk factors may contribute to it, and recent reports have suggested the importance of genetic factors as well. The COL9A2 gene, which codes for one of the polypeptide chains of collagen IX that is expressed in the intervertebral disc, was screened for sequence variations in individuals with intervertebral disc disease. The analysis identified a putative disease-causing sequence variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
200
1
4

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 331 publications
(218 citation statements)
references
References 40 publications
5
200
1
4
Order By: Relevance
“…Another explanation could be that VESC is more prevalent in Europe, perhaps on the basis of specific genes that are associated with (1) an increased risk of tissue injury, (2) and increased response to injury, or (3) a decreased ability to heal injured tissue. In support of this theory, there are different prevalence rates of genes associated with disc degeneration for individuals from Northern Europe as compared to Asian populations [5,67,112,128,147]. Also, a recent study suggests that VESC may be related to increased response to injury, as a combination of specific genes (IL1A and MMP-3) increased the odds of having type 2 changes by eight times [73].…”
Section: Discussionmentioning
confidence: 71%
“…Another explanation could be that VESC is more prevalent in Europe, perhaps on the basis of specific genes that are associated with (1) an increased risk of tissue injury, (2) and increased response to injury, or (3) a decreased ability to heal injured tissue. In support of this theory, there are different prevalence rates of genes associated with disc degeneration for individuals from Northern Europe as compared to Asian populations [5,67,112,128,147]. Also, a recent study suggests that VESC may be related to increased response to injury, as a combination of specific genes (IL1A and MMP-3) increased the odds of having type 2 changes by eight times [73].…”
Section: Discussionmentioning
confidence: 71%
“…Whether the degeneration is the result of a loss of mechanical integrity in the disc or the mechanical loading itself being a precipitating factor of the degeneration, is still unresolved [1,82]. Recent evidence suggests that genetic factors are also important [5,11,28,68,80]. Nonetheless, degeneration of IVDs has been characterized extensively indicating that degeneration involves changes in disc morphology, composition of ECM, as well as loss of disc cells, proteoglycan and water content.…”
Section: Intervertebral Disc Degenerationmentioning
confidence: 99%
“…Several studies have found familial predisposition to LDD, including early onset sciatica and lumbar disc herniation. In addition, mutations or polymorphisms in several genes have been reported to be associated with either the presence or severity of disc degeneration, including gene coding for collagen IX and XI [2,12,13], aggrecan [9], cartilage intermediate layer protein [18], vitamin D receptor [22], interleukin-1 [19], matrix metalloproteinase-3(MMP-3) [20], tissue inhibitor of metalloproteinase-1(TIMP-1) [21], and cyclooxygenase-2 [21].…”
Section: Introductionmentioning
confidence: 99%